ANALISIS KEPUTUSAN PEMBELIAN PADA PERUSAHAAN JASA PENGIRIMAN - Fitriani Lestari, (2020)
This research is using a quantitative study aimed to see whether there is an influence of service quality, location, and e-word of mouth on a purchase decision. This research uses descriptive and verification approaches. The sample in this research amounted to 130 J&T users located in Jakarta using probability sampling technique. Data were collected through questionnaire. Data analysis techniques were processed using Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The result shows that: (1) The service quality has a positive and significant effect on purchase decision (2) Location has no effect on purchase decision; (3) E-word of mouth has a positive and significant effect on purchase decision The coefficient of determination R2 is 0.772 or it can be interpreted that 77.2% of purchase decision at J&T shipping service company in Jakarta are affected by service quality, location, and e-word of mouth variables, while the rest are affected by other variables outside this research.